2002
DOI: 10.1046/j.1365-313x.2002.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Barley stripe mosaic virus‐induced gene silencing in a monocot plant

Abstract: SummaryRNA silencing of endogenous plant genes can be achieved by virus-mediated, transient expression of homologous gene fragments. This powerful, reverse genetic approach, known as virus-induced gene silencing (VIGS), has been demonstrated only in dicot plant species, where it has become an important tool for functional genomics. Barley stripe mosaic virus (BSMV) is a tripartite, positive-sense RNA virus that infects many agriculturally important monocot species including barley, oats, wheat and maize. To de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
538
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(573 citation statements)
references
References 58 publications
(91 reference statements)
14
538
0
7
Order By: Relevance
“…Moreover, multiple disease evaluations can be conducted for Rphq4 in individual plants by inoculation of the fourth leaf to the Xag leaf, respectively, enabling a more reliable evaluation of Rphq4 in a single plant. Barley stripe mosaic virus-induced gene silencing (BSMV-VIGS) is an important tool for the analysis of gene function in barley (Holzberg et al 2002;Lacomme et al 2003) and has been successfully used to deWne the function of important genes (Hein et al 2005;Shen et al 2007). In BSMV-VIGS system, photobleaching symptoms were usually observed approximately 3 weeks after the viral inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multiple disease evaluations can be conducted for Rphq4 in individual plants by inoculation of the fourth leaf to the Xag leaf, respectively, enabling a more reliable evaluation of Rphq4 in a single plant. Barley stripe mosaic virus-induced gene silencing (BSMV-VIGS) is an important tool for the analysis of gene function in barley (Holzberg et al 2002;Lacomme et al 2003) and has been successfully used to deWne the function of important genes (Hein et al 2005;Shen et al 2007). In BSMV-VIGS system, photobleaching symptoms were usually observed approximately 3 weeks after the viral inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…At the three‐leaf stage, at least 20 plants of CI12633 were inoculated with BSMV:TaRCR1 or BSMV:00 (as a control) following Holzberg et al . (2002). At 10 day after virus infection, the fourth leaves were collected to monitor BSMV infection and to evaluate the transcript changes of TaRCR1 .…”
Section: Methodsmentioning
confidence: 99%
“…The upper limit for RNAi trigger size is less defined, with successful examples in wheat of up to 683 bp (Li et al 2005) and in barley VIGS of up to 1,215 bp (Holzberg et al 2002). The determination of the upper limit for RNAi trigger size may be also related to the number of targets that can be effectively included in a single RNAi construct to knockdown multiple target transcripts.…”
Section: Rnai Trigger Sizementioning
confidence: 99%
“…To date, VIGS has had broad application in dicots (Burch-Smith et al 2004) and has also proven to be feasible in barley when using engineered Barley Stripe Mosaic Virus (BSMV) vectors (Holzberg et al 2002). Using PDS and the visible photobleaching phenotype, Holzberg et al (2002) showed that the BSMV-VIGS system elicits target-directed gene silencing in barley in a sequence dependent manner.…”
Section: Transient Rnai In Wheat Through Virus Induced Gene Silencingmentioning
confidence: 99%
See 1 more Smart Citation